The Challenges and Solutions for Cadmium-contaminated Rice in China: A Critical Review - Hu, Yuanan; Cheng, Hefa; Tao, Shu (Environment international, 2016)
The wide occurrence of Cd-contaminated rice in southern China poses significant public health risk and deserves immediate action, which arises primarily from extensive metal (including Cd) contamination of paddies with the fast expansion of nonferrous metal mining and smelting activities. Accumulation of Cd in rice grains can be reduced by removing Cd from the contaminated paddy soils, reducing its bioavailability, and controlling its uptake by rice plants. Although a range of measures can be taken to rehabilitate Cd-contaminated lands, including soil replacement and turnover, chemical washing, and phytoremediation, they are either too expensive and/or too slow. Various amendment materials, including lime, animal manures, and biochar, can be used to immobilize Cd in soils, but such fixation approach can only temporarily reduce Cd availability to rice uptake. Cultivation of alternative crops with low Cd accumulation in edible plant parts is impractical on large scales due to extensive contamination and food security concerns in southern China. Transgenic techniques can help develop rice cultivars with low Cd accumulation in grains, but little public acceptance is expected for such products. As an alternative, selection and development of low-Cd rice varieties and hybrids through plant biotechnology and breeding, particularly, by integration of marker-assisted selection (MAS) with traditional breeding, could be a practical and acceptable option that would allow continued rice production in soils with high bioavailability of Cd. Plant biotechnology and breeding can also help develop Cd-hyperaccumulating rice varieties, which can greatly facilitate phytoremediation of contaminated paddies. To eliminate the long-term risk of Cd entering the food chain, soils contaminated by Cd should be cleaned up when cost-effective remediation measures are available. [Display omitted] •Cd-contaminated rice poses major food safety and public health concerns in S. China•Cd pollution of paddies resulted primarily from nonferrous metal mining and smelting•Removal of Cd from soil is challenging, while its phytoavailability can be controlled•Plant biotechnology and breeding can accelerate development of low-Cd rice cultivars•Growing low-Cd rice in contaminated paddies can greatly reduce dietary exposure of Cd